Evaluation of two endometriosis models by transplantation of human endometrial tissue fragments and human endometrial mesenchymal cells - Mina Jafarabadi; Mojdeh Salehnia; Rana Sadafi (Shahid Sadoughi University of Medical Sciences, 2017)
Background: The animal models of endometriosis could be a valuable alternative tool for clarifying the etiology of endometriosis. Objective: In this study two endometriosis models at the morphological and molecular levels was evaluated and compared. Materials and Methods: The human endometrial tissues were cut into small fragments then they were randomly considered for transplantation into γ irradiated mice as model A; or they were isolated and cultured up to fourth passages. 2×106 cultured stromal cells were transplanted into γ irradiated mice subcutaneously as model B. twenty days later the ectopic tissues in both models were studied morphologically by Periodic acid-Schiff and hematoxylin and eosin staining. The expression of osteopontin (OPN) and matrix metalloproteinase 2 (MMP2) genes were also assessed using real time RT-PCR. 17-β estradiol levels of mice sera were compared before and after transplantation. Results: The endometrial like glands and stromal cells were formed in the implanted subcutaneous tissue of both endometriosis models. The gland sections per cubic millimeter, the expression of OPN and MMP2 genes and the level of 17-β estradiol were higher in model B than model A (p=0.03). Conclusion: Our observation demonstrated that endometrial mesenchymal stromal cells showed more efficiency to establish endometriosis model than human endometrial tissue fragments